Night of the Hunter - Schumann, Walter (Bear Family Records, 1998)
Almost lost in the shuffle is this recording, originally released by RCA Victor in 1955, which has since become a collector's item, and justly so. Unlike most soundtrack recordings, this one integrates the film's music with a reading by Charles Laughton of the story, beautifully written for the recording itself. [www.amazon.com]
Keywords: CD